PENGARUH KONSENTRASI 6-Benzyl Aminopurine (BAP) PADA MEDIA MS TERHADAP INDUKSI KULTUR JARINGAN CAKRAM BAWANG MERAH (Allium ascalonicum L.) - Fitriya Pebriana; Sri Wiyatiningsih; Pangesti Nugrahani (UPN VETERAN JAWA TIMUR, 2018)
Aim of the research is to determine the optimum concentration that has the best effect on the tissue culture induction of onion discus. This research was carried out in August to November 2017, in Biotechnology Laboratory, Agriculture Faculty, UPN